Recent advances in one-dimensional halide perovskites for optoelectronic applications - Qiu, T.; Hu, Y.; Xu, F.; Yan, Z.; Bai, F.; Jia, Guohua; Zhang, S. (R S C Publications, 2018)
Metal-halide perovskites have emerged as efficient, low-cost energy materials owing to their remarkable optoelectronic properties. In particular, the dimensionality and morphology of crystallites may have a striking influence on their chemical and physical properties and therefore affect their optoelectronic applications. One-dimensional halide perovskites have superior carrier transportation in one dimension, high crystalline quality, and consequently, high quantum efficiencies and long carrier diffusion lengths, which are important for the performance of perovskite-based nanoscale optoelectronic and photonic devices. In this review, we highlight recent advances in the synthesis of one-dimensional halide perovskites and their unique properties as well as their novel optoelectronic applications. This review aims to provide an overview of the achievements in synthesis techniques and nanoscale optoelectronic applications based on one-dimensional perovskite nanocrystals.